Three-dimensional left atrial strain from retrospective gated computed tomography: Comparison with speckle-tracking echocardiography in patients with aortic stenosis - Sillett, Charles; Androshchuk, Vitaliy; Long, Edouard; Baptiste, Tiffany M.G.; Strocchi, Marina; Solis Lemus, Jose Alonso; Lee, Angela WC; Roney, Caroline H.; Rajani, Ronak; Patterson, Tiffany; Redwood, Simon; Niederer, Steven A. (Journal of cardiovascular computed tomography, 2025)
Three-dimensional (3D) left atrial (LA) deformation assessment beyond the two-dimensional (2D) apical views circumvents atrial foreshortening and can be quantified from four-dimensional (4D) retrospective gated computed tomography (CT) using novel feature tracking methods. However, the consistency between CT-derived 3D and echocardiographic 2D peak left atrial longitudinal strain (PALS) has not been reported. We aimed to compare CT-derived 3D and echocardiographic 2D PALS in patients undergoing transcatheter aortic valve implantation (TAVI). Eighty patients (81.8 ​± ​5.8 years, 30 ​% female) who underwent CT and transthoracic echocardiography (TTE) before TAVI were included. CT images were reconstructed at 5 ​% increments over the R–R interval. 4D CT-derived deformation was evaluated using novel feature tracking, from which 2D and 3D PALSCT were measured and compared with 2D PALSTTE. 2D PALSTTE and 2D PALSCT measurements were strongly correlated (Pearson coefficient ​= ​0.84) and comparable (mean bias ​= ​−0.8; 95 ​% confidence interval, CI: -1.9 to 0.3), whereas 2D PALSTTE exhibited systematic overestimation compared with 3D PALSCT (mean bias ​= ​−3.6; 95 ​% CI: -4.7 to −2.5; P ​< ​0.001). 3D PALSCT and 2D PALSTTE exhibited comparable correlations with exercise capacity and quality of life scores and prediction of elevated brain natriuretic peptide (area under the curve, AUC: 0.84, 0.79, respectively) and diastolic filling pressures (AUC: 0.65, 0.69, respectively). 2D PALSCT and 2D PALSTTE showed good agreement, whereas 2D PALSTTE was systemically larger than 3D PALSCT which may be attributed to atrial foreshortening. 3D PALSCT circumvents limitations of 2D echocardiography and may offer adjunctive evaluation of atrial reservoir function in patients with valvular heart disease. A: 2D PALSTTE from STE. B: 3D PALSCT from multi-phase CT. C: Inter-modality correlation (top) and Bland-Altman analysis (bottom). D: Association with elevated brain natriuretic peptide (top) and diastolic filling pressures using E/e’ (bottom). PALS, peak left atrial longitudinal strain; TTE, transthoracic echocardiography; CT, computed tomography; BNP, brain natriuretic peptide. [Display omitted]